High-performance Co-PDA-CF catalyst fabrication and lifetime prediction model for electrosynthesis of hydrogen peroxide. (10th December 2022) - Fu, Dengyu; Zhu, Yanji; Chen, Lei; Cui, Yexiang; Bao, Di; Sun, Yue; Zhang, Meng; Wang, Huaiyuan
Highlights: Directly applicable Co, polydopamine co-modified carbon felt catalytic cathode for H2 O2 production. Co, polydopamine synergistic effect of the catalytic cathode exhibits excellent H2 O2 production activity. Correlation of different factors influences on catalyst remaining lifetime prediction. Correlation of different modified carbon felt catalysts H2 O2 production activity and lifetime prediction method. Abstract: Cathode oxygen reduction to produce hydrogen peroxide (H2 O2 ) has been widely studied due to its mild reaction conditions and environmentally friendly properties. The development of electrocatalytic H2 O2 production industry not only depends on the high-performance catalysts research, but also the catalysts' lifetime prediction, which plays an important role in production stability and sustainability. Here, a series of polydopamine (PDA) and metal ions (M = Fe 2+, Zn 2+, Ni 2+ and Co 2+ ) co-modified carbon felt catalysts are successfully synthesized by hydration method. Among them, Co 2+ and PDA co-modified carbon felt (Co-PDA-CF) catalyst exhibits excellent H2 O2 production performance, which is 14 times higher than that of the raw carbon felt (R-CF). The characterization result indicates that the excellent H2 O2 production performance is attributed to synergistic effect of Co, PDA and the improved interfacial properties. In addition, a catalyst lifetime prediction model for H2 O2 production by cathode oxygen reduction (2e − ORR) is established for the first time. By investigating different factors influence on the catalyst activity change, a two-parameter 2e − ORR catalyst lifetime prediction model is established. Besides, through studying the activity change law of different catalysts in H2 O2 production process, correlation model based on different catalysts for lifetime prediction is established, by which the unknown carbon felt supported catalyst lifetime can be predicted. We believe that our research will provide insights into advanced 2e − ORR catalyst fabrication. And the proposed lifetime prediction model will provide guidance on lifetime management of 2e − ORR catalysts and even other gas-liquid-solid three-phase interface reaction process. Graphical abstract: Image, graphical abstract